Analisis Prediksi Kebangkrutan Pada Bank Umum Syariah di Indonesia Menggunakan Metode Fulmer Periode 2010-2019 - Kusumanisita, Apriliana Ika; Musdalifh, Istiana Mita (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
This research is used to predict early bankruptcy in the health of financial performance in the Islamic banking industry in Indonesia using the Fulmer method. This research uses a quantitative approach. The data analysis technique used is the regression of the panel data. The samples used in this study are 14 Islamic commercial banks that have been registered with Bank Indonesia. The sampling technique uses the purposive sampling method because researchers determine certain criteria for Islamic commercial banks that have published their financial statements. The data used by researchers is secondary data which means using data collected in the form of financial statements. The results of this study showed the value of R square 0.998771 means that 99% prediction on the variable Fulmer method can explain the level of health of the financial performance of sharia commercial banks. In addition, the results of this study also showed that simultaneous and partial variables of Fulmer methods had a significant positive effect on bankruptcy in Islamic commercial banks.